CD-Based Microfluidics for Primary Care in Extreme Point-of-Care Settings - Suzanne Smith; Dario Mager; Alexandra Perebikovsky; Ehsan Shamloo; David Kinahan; Rohit Mishra; Saraí M. Torres Delgado; Horacio Kido; Satadal Saha; Jens Ducrée; Marc Madou; Kevin Land; et al. (Micromachines, 2016)
We review the utility of centrifugal microfluidic technologies applied to point-of-care diagnosis in extremely under-resourced environments. The various challenges faced in these settings are showcased, using areas in India and Africa as examples. Measures for the ability of integrated devices to effectively address point-of-care challenges are highlighted, and centrifugal, often termed CD-based microfluidic technologies, technologies are presented as a promising platform to address these challenges. We describe the advantages of centrifugal liquid handling, as well as the ability of a standard CD player to perform a number of common laboratory tests, fulfilling the role of an integrated lab-on-a-CD. Innovative centrifugal approaches for point-of-care in extremely resource-poor settings are highlighted, including sensing and detection strategies, smart power sources and biomimetic inspiration for environmental control. The evolution of centrifugal microfluidics, along with examples of commercial and advanced prototype centrifugal microfluidic systems, is presented, illustrating the success of deployment at the point-of-care. A close fit of emerging centrifugal systems to address a critical panel of tests for under-resourced clinic settings, formulated by medical experts, is demonstrated. This emphasizes the potential of centrifugal microfluidic technologies to be applied effectively to extremely challenging point-of-care scenarios and in playing a role in improving primary care in resource-limited settings across the developing world.